Trend of fast food consumption among university girls in Karachi, Pakistan - Ismail, Iqra (International Journal of Endorsing Health Science Research, 2016)
Background The present study is aimed at improving the understanding of fast food trend among university girls. Objectives To study the trend of fast food consumption among university girls and to find out the association between university girls’ perception regarding the unhealthfulness of fast food and their frequency of eating fast food. Methods A sample size of 50 female university students was selected for data collection through purposive sampling. By using questionnaire method, respondents were asked about their trend of fast food consumption by inquiring about their fast food preferences, their consumption pattern, and their monthly fast food expenditure. Correlation was used to analyze the association between the perception regarding the unhealthfulness of fast food and frequency of eating fast food. Results We found that the most preferred fast food item among university girls was burger (44.7%). The majority of respondents consume fast food at an average of 2-3 times a month (29.8%) and the main reason for their fast food consumption was convenience (55.3%). Among those who infrequently consume fast food, a majority (90%) agreed to the statement that fast food is unhealthful whereas among those who frequently consume fast food, a comparatively low percent (77.7%) agreed to the statement. Through correlation, we observed no association between all of the asked perceptions regarding fast food and frequency of fast food consumption among university girls (p >0.05). Conclusion The overall results showed that university girls’ perception regarding the unhealthfulness of fast food does not necessarily affect their frequency of fast food consumption.